Estudo de comunidades incrustantes sobre painéis experimentais em três áreas da Baía de Guanabara, RJ, Brasil - Zalmon, Ilana Rosental (1988)
In the present work are reported the results of the study of fouling communities wich have been developed in artificial substrata using monthly and cumulative panels, during a year in the regions of Guanabara Bay: Urca Beach, Governador Island and Paquetá Island. Quantitative and qualitative data about the fouling organisms and also environmental parameters such as temperature, salinity, pH, dissolved oxygen (D.O) biochemical oxygen demand (B.O.D) ammonia, nitrite and nitrate were analysed.